Improving Newborn Survival in Southern Tanzania (INSIST) trial; community-based maternal and newborn care economic analysis - Manzi, Fatuma (Health Policy Plan, 2017)
Despite health systems improvements in Tanzania, gaps in the continuum of care for maternal, newborn and child health persist. Recent improvements have largely benefited those over one month of age, leading to a greater proportion of under-five mortality in newborns. Community health workers providing home-based counselling have been championed as uniquely qualified to reach the poorest. We provide financial and economic costs of a volunteer home-based counselling programme in southern Tanzania. Financial costs of the programme were extracted from project accounts. Ministry of Health and Social Welfare costs associated with programme implementation were collected based on staff and project monthly activity plans. Household costs associated with facility-based delivery were also estimated based on exit interviews with post-natal women. Time spent on the programme by implementers was assessed by interviews conducted with volunteers and health staff. The programme involved substantial design and set-up costs. The main drivers of set-up costs were activities related to volunteer training. Total annualized costs (design, set-up and implementation) amounted to nearly US$300 000 for financial costs and just over US$400 000 for economic costs. Volunteers (n = 842) spent just under 14 hours per month on programme-related activities. When volunteer time was valued under economic costs, this input amounted to just under half of the costs of implementation. The economic consequences of increased service use to households were estimated at US$36 985. The intervention cost per mother–newborn pair visited was between US$12.60 and US$19.50, and the incremental cost per additional facility-based delivery ranged from US$85.50 to US$137.20 for financial and economic costs (with household costs). Three scale-up scenarios were considered, with the financial cost per home visit respectively varying from $1.44 to $3.21 across scenarios. Cost-effectiveness compares well with supply-side initiatives to increase coverage of facility-based deliveries, and the intervention would benefit from substantial economies of scale.